Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Des femmes respectables : classe et genre en milieu populaire - Skeggs, Beverley (Agone, 2015)
La matière première de ce livre est une série d'entretiens menés par Beverley Skeggs avec quatre-vingt-trois jeunes femmes issues de la classe ouvrière anglaise, inscrites à une formation d'aide à la personne et travaillées par leur propre respectabilité. Abordant leur rapport à la sexualité, à la classe ou au féminisme, cet ouvrage vient apporter un prolongement essentiel aux travaux de Pierre Bourdieu et de Paul Willis.
Édition originale : B. Skeggs, Formations of Class & Gender. Becoming Respectable, Sage, 1997
Keywords: 1900-1999; 1980-1989; 1990-1999; analyse de discours; angleterre; approches et analyses; care; classe ouvrière; classe sociale; cours; cultural studies; cycles supérieurs; discipline; ethnographie; europe; fem7000; fémininité; féminisme marxiste; histoire et politique; point de vue situé; périodes historiques; rapports sociaux de sexe; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sciences sociales; sexualité; sociologie; thématiques; épistémologie